ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP AUDIT REPORT LAG (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2015) - Butarbutar, Rizki Sakti Kornelius; Hadiprajitno, P. Basuki (Diponegoro Journal of Accounting, 2017)
The purpose of this research is to analyze the factors that affect audit report lag of financial reports to the manufacturing companies listed on the Indonesia Stock Exchange. The examined factors of this research are corporate size, audit firm status, complexity of the company’s operation, board size, audit committee, ownership dispersion, and ownership concentration as the independent variable, while the audit report lag as the dependent variable.The sample consists of 410 companies listed in the Indonesia Stock Exchange (IDX) and submitted financial reports to OJK in the period 2012-2015. The data that was used in this research was secondary data and selected by using purposive sampling method. Model analysis using multiple linear regression analysis. Using the F-test to determine the effect of simultaneous between company characteristics and capital structure. Using t-test to examine the partial correlation of each independent variable on audit report lag.Based on analytical results shows that variable board size have significant influence toward audit report lag, while variable corporate size, audit firm status, complexity of the company’s operation, audit committee, ownership dispersion, and ownership concentration doesn’t have significant influence toward audit report lag.